2024
DOI: 10.1051/0004-6361/202348212
|View full text |Cite
|
Sign up to set email alerts
|

AGNs in massive galaxy clusters: Role of galaxy merging, infalling groups, cluster mass, and dynamical state

E. Koulouridis,
A. Gkini,
E. Drigga

Abstract: There is compelling evidence that active galactic nuclei (AGNs) in high-density regions have undergone a different evolution than their counterparts in the field, indicating that they are strongly affected by their environment. However, we still lack a comprehensive understanding of the dominant mechanisms that trigger the nucleus and the processes that drive the evolution of AGNs in clusters. To investigate (and possibly disentangle) the various factors that may affect the prevalence of AGNs in cluster galaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Contrasting mergers with relaxed clusters, Stroe & Sobral (2021) found an even distribution of star formation galaxies within 3 Mpc of merging cluster centers but noted their rarity in relaxed clusters. Interestingly, they observed AGN primarily in relaxed cluster outskirts (∼1.5-3 Mpc; see also Koulouridis et al 2018Koulouridis et al , 2024Koulouridis & Bartalucci 2019). However, Wittman et al (2024) found no correlation between starforming/AGN fractions and the time since pericenter.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting mergers with relaxed clusters, Stroe & Sobral (2021) found an even distribution of star formation galaxies within 3 Mpc of merging cluster centers but noted their rarity in relaxed clusters. Interestingly, they observed AGN primarily in relaxed cluster outskirts (∼1.5-3 Mpc; see also Koulouridis et al 2018Koulouridis et al , 2024Koulouridis & Bartalucci 2019). However, Wittman et al (2024) found no correlation between starforming/AGN fractions and the time since pericenter.…”
Section: Discussionmentioning
confidence: 99%
“…It is often defined as the number of AGNs within the member galaxies of a cluster. Many researchers have investigated the AGN number fraction for galaxy groups and clusters (e.g., Krick et al 2009;Martini et al 2009;Tomczak et al 2011;Pentericci et al 2013;Ehlert et al 2014;Magliocchetti et al 2018;Koulouridis & Bartalucci 2019;Koulouridis et al 2024). In addition, this parameter has been explored using semianalytic galaxy Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%